Effects of Ashwagandha Supplementation on Strength, Endurance, and Post-Exercise Recovery: A Review - Prokopczyk, Kamila; Peszt, Michał Józef; Jakubowska, Paulina; Poręba, Kacper; Poręba, Martyna; Wasilczuk, Antoni; Szaryński, Mikołaj; Lewandowska-Mackiewicz, Aleksandra; Rusiłowicz, Rafał; Matuszewska, Julia; et al. (Quality in Sport, 2025)
Introduction: Ashwagandha (Withania somnifera) is a traditional adaptogenic herb widely used in Ayurveda – traditional Indian medicine. Recent studies have investigated its potential benefits in sports and physical activity, including improvements in cardiorespiratory fitness, muscle strength, recovery, and psychophysiological adaptation. Its effects are attributed to adaptogenic, antioxidant, anti-inflammatory properties, and modulation of hormonal responses. Aim of the study: The aim of this study is to review the scientific literature regarding the effects of Ashwagandha supplementation on parameters relevant to sports performance. Materials and Methods: An extensive literature research was conducted in the PubMed database up to the year 2025. Summary: Evidence indicates that Ashwagandha supplementation provides multidimensional benefits in sports and physical activity. Improvements include increased VO₂max, extended time to exhaustion, enhanced muscle strength and lean body mass, and increased arm circumference and testosterone levels. Ashwagandha also supports recovery by reducing perceived fatigue, improving sleep quality, decreasing exercise-induced muscle enzyme elevation, and lowering inflammatory markers such as CRP. Additional effects include antioxidant protection, reduced oxidative stress, and favorable hormonal modulation (e.g., cortisol reduction of 27–30%, increased testosterone). Conclusions: Ashwagandha appears to be a safe and promising supplement for enhancing performance, strength, and recovery. However, due to methodological limitations, variability in dosing, and heterogeneity of study populations, its use should be guided by individual assessment and consultation with a qualified professional. Further well-designed clinical trials are needed to establish optimal supplementation protocols and long-term effects.